How to effectively reverse life-thretening effects of non-vitamin K oral anticoagulants? - Łukasz Wołowiec; Joanna Banach; Daniel Rogowicz; Magdalena Węglarz; Walery Zukow; Władysław Sinkiewicz (Kazimierz Wielki University, 2017)
For several decades the vitamin K antagonist oral anticoagulants were the only outpatient therapy that existed to reduce the risk of stroke and thromboembolism until non-vitamin K oral anticoagulants (NOACs). Direct thrombin inhibitor: dabigatran and factor Xa inhibitors: apixaban, rivaroxaban, and edoxaban directly inhibit the coagulation cascade. DOACs have many advantages over warfarin. In general, the new agents have similar or lower bleeding risk than vitamin K antagonists, especially risk of intracranial bleeding. However, the biggest drawback of DOACs has been the lack of specific antidotes to reverse the anticoagulant effect in emergency situations. New specific antidotes (idarucizumab, andexanet alfa, and ciraparantag) show promising data, and may soon become available for clinical use. In this article, we review the pharmacology of these agents, outcomes of their use, and the more recent advances for the development of specific antidotes.